Prolonged Survival of Subcutaneous Allogeneic Islet Graft by Donor Chimerism without Immunosuppressive Treatment - Brend Ray-Sea Hsu; Shin-Huei Fu; Aline Yen Ling Wang (International Journal of Endocrinology)
The aim of this study was to investigate whether tolerance-induced protection of islets in the renal subcapsular space can also prevent subcutaneous allogeneic islets from being rejected. We used bone marrow stem cells from C57BL/6 (H2b) mice to construct donor chimerism in conditioned diabetic BALB/c (H2d) mice and investigated the effect of donor chimerism on engraftment and survival of subcutaneously transplanted allogeneic islets in streptozotocin-induced diabetic mice. We also studied the anti-inflammatory effect of mesenchymal stem cell on islet engraftment. Full but not low-grade or no donor chimerism was associated with successful engraftment of allogeneic islets and restoration of normoglycemia in the treated diabetic mice. The temporary hyperglycemia was 11 ± 1 versus 19 ± 5 days (p<0.05) for the mice with full donor chimerism with transplanted islets in the renal subcapsular space versus the subcutaneous space, respectively. Cotransplantation of mesenchymal stem cell did not enhance alloislet engraftment. Full multilineage donor chimerism was associated with a higher transient expansion of CD11b+ and Gr-1+ myeloid progenitor cells and effector memory CD4 and CD8 T cells. In conclusion, full donor chimerism protected both renal subcapsular and subcutaneous allogeneic islets in this rodent transplantation model.